Waist Circumference was Positively Correlated with Chemerin, Retinol-Binding Protein 4 and hsCRP - Lucia Herminawati; Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Central obesity is associated with various chronic metabolic disorders characterized by abnormal cytokine production, increased acute phase reactants, and activation of inflammatory signaling pathways. This study was aimed to investigate the association of waist circumference, chemerin, and retinol binding protein (RBP)-4 with inflammation in men with central obesity.METHODS: The research was conducted with a crosssectional design involving 68 centrally obese male subjects aged 30 to 60 years old, with waist circumference (WC) >90 cm. All subjects fulfilled the inclusion and exclusion criteria. Anthropometric parameters, fasting glucose, creatinine, SGOT, SGPT and hsCRP were measured. Serum concentrations of chemerin and RBP4 were measured by ELISA.RESULTS: The trend lines showed that chemerin, RBP4, and hsCRP increased with WC. Pearson correlation test showed a positively significant correlation between WC and hsCRP (r=0.242, p<0.05); and also between chemerin and hsCRP (r=0.244, p<0.05) and RBP4 (r=0.321, p<0.01). Subjects were stratified into four groups based on their chemerin and RBP4 levels (high chemerin/high RBP4, high chemerin/low RBP4, low chemerin/high RBP4, or low chemerin/low RBP4). Subjects who were in the high chemerin/low RBP4 group were more likely to have high level of inflammation (47.6%), but subjects with high chemerin/high RBP4 showed low level of inflammation (42.9%) as compared with the other three groups.CONCLUSIONS: We concluded that increased WC was correlated with elevated levels of chemerin, RBP4, and hsCRP. High chemerin was correlated with increased level of RBP4 as well as with high level of inflammation.KEYWORDS: waist circumference, chemerin, RBP4, hsCRP, inflammation